Seasonal Variations in the Chemical Composition of Apple Snail, Pila globosa (Bangladesh Journal of Scientific and Industrial Research, 2012)
Protein, carbohydrate, fat, ash and moisture content in the muscle of Pila globosa (Swainson) were analyzed. The compositions varied seasonally  in relation to reproductive cycle of the snail. Significant correlation existed between moisture and carbohydrate (r = 0.79), moisture  and fat (r = 0.74), moisture and protein (r = 0.94), moisture and ash (r = 0.73), protein and ash (r = 0.80), fat and carbohydrate (r =  0.95), protein and carbohydrate (r = 0.89) in females. In male, correlation is highly significant between protein and ash ( r= 0.65), protein  and carbohydrate (r= 0.49), fat and carbohydrate ( r= 89). But negatively correlated with moisture and fat (r = -0.38), moisture and carbohydrate  (r = -0.40) ,), moisture and ash (r = - 0.30), moisture and protein (r = - 0.13). Fat and carbohydrate content was higher in large sized  female than that of the male.DOI: http://dx.doi.org/10.3329/bjsir.v47i1.10730 Bangladesh J. Sci. Ind. Res. 47(1), 89-92, 2012